A method for testing particle size distribution of positive electrode materials for lithium-ion batteries
By combining solvent dispersion and deposition methods with laser particle size analyzer and scanning electron microscope detection, the problem of detecting large agglomerates of lithium-ion battery cathode materials has been solved, simplifying the operation and improving the detection accuracy.
Patent Information
- Application Number
- CN202411336462.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-25
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2044-09-25
AI Technical Summary
Existing technologies are insufficient to effectively detect the large agglomerates of nanoparticles formed during the stirring process in lithium-ion battery cathode materials, which leads to bumps during coating. Furthermore, traditional detection methods are complex and cannot obtain quantitative data.
Solvent dispersion and deposition methods were combined with laser particle size analyzer and scanning electron microscope for detection. The dispersion process of battery slurry was simulated by repeated dispersion deposition and ultrasonic or mechanical stirring. Large particles were enriched and then particle size was detected.
It simplifies the operation process, reduces material consumption, and can accurately detect the particle size distribution of large agglomerated particles in slurry, thus improving the operability and accuracy of the detection.
Smart Images

Figure CN118858085B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of lithium ion batteries, and in particular relates to a method for testing the particle size distribution of a lithium ion battery positive electrode material. Background Art
[0002] Lithium-ion batteries have gradually become the focus of attention in new chemical energy sources due to their advantages such as large specific capacity, good cycle performance, high operating voltage, long service life and low pollution. At present, lithium-ion batteries are widely used in digital products such as mobile phones and computers, new energy vehicles and energy storage. However, with the increasing demand for new energy electric vehicles and electric buses, higher requirements are placed on the energy density, power and cycle life of lithium-ion batteries. The battery is mainly composed of four parts: positive electrode material, negative electrode material, electrolyte and battery separator. Its performance mainly depends on the structure and performance of the internal materials used in the battery. Studies have found that the particle size distribution of the positive electrode of lithium-ion batteries is very critical to the processing performance of lithium-ion batteries such as pulping and coating, so the particle size distribution of the positive electrode material has always been a key indicator that must be checked. Due to factors such as complex particle shape and wide particle size distribution, how to effectively monitor the particle size distribution of the positive electrode material is also one of the difficulties in the industry.
[0003] At present, the industry generally uses a laser particle size analyzer to measure conventional particle size distribution, combined with screening particle size and scanning electron microscope micro-area morphology to monitor the particle size distribution of positive electrode materials. The classic operating steps for testing particle size distribution in the industry are: use a suitable medium to disperse the positive electrode material with the assistance of an ultrasonic cleaner, and then use the laser particle size analyzer operating procedures for testing. When there are nano-scale particles in the positive electrode material, these nano-particles may agglomerate into large particles due to stirring during the actual production of the slurry. When the positive electrode material containing large agglomerated particles is used in the slurry coating, convex points will appear on the pole piece, resulting in the production of defective products. However, due to the limitation of the injection volume, the laser particle size analyzer cannot detect this small proportion of large agglomerated particles when detecting the sample. At present, the main method used is screening to screen out these large agglomerated particles and then observe them using a scanning electron microscope. This method consumes a large amount of positive electrode materials, is complicated to operate, and cannot obtain quantitative data in a statistical sense. Summary of the invention
[0004] The technical problem to be solved by the present invention is to overcome the deficiencies and defects mentioned in the above background technology, provide a testing method for the particle size distribution of positive electrode materials for lithium ion batteries, realize the particle size detection of agglomerated particles formed during the stirring process of the positive electrode materials, and simplify the operation process.
[0005] The purpose of the present invention can be achieved through the following technical solutions:
[0006] The present invention provides a method for testing the particle size distribution of a lithium ion battery positive electrode material, comprising the following steps:
[0007] S1. Deposition: Take lithium iron phosphate positive electrode powder material, disperse it in a solvent to obtain a mixture, let the mixture stand for 2-3 minutes, pour out the upper solid-liquid mixture, and obtain a deposited powder;
[0008] S2, repeated dispersion and deposition: repeat the dispersion and deposition operation steps of S1 for the deposited powder, repeat the dispersion and deposition 2-4 times to prepare the sample to be tested;
[0009] S3, laser particle size analyzer detection: the sample to be tested obtained in S2 is dispersed in a solvent and added to a laser particle size analyzer to test the particle size distribution;
[0010] S4. Scanning electron microscope detection: The sample to be tested obtained in S2 is filtered and dried, and adhered to the sample stage of the scanning electron microscope with a conductive tape. The particle size of large particles is observed under the scanning electron microscope.
[0011] Furthermore, the sampling amount of the lithium iron phosphate positive electrode powder material is 20-50g.
[0012] Furthermore, the solvent is one of ultrapure water, anhydrous ethanol and N-methylpyrrolidone.
[0013] Furthermore, the mass ratio of the lithium iron phosphate positive electrode powder material to the solvent in the mixture is 1:1-4.
[0014] Furthermore, the dispersion method in S1 is one of ultrasonic dispersion and mechanical stirring dispersion, the ultrasonic frequency is 53KHz, and the mechanical stirring speed is 1000rpm.
[0015] Furthermore, the dispersion time in S1 is 30 minutes.
[0016] Furthermore, the single solvent dosage in the repeated dispersion deposition is 20-30 mL.
[0017] Furthermore, in the repeated dispersion deposition, the single dispersion time is 10 minutes, and the single standing time is 2-3 minutes.
[0018] Furthermore, the particle size of the sample to be tested is 0.1-55 μm.
[0019] Beneficial effects of the present invention:
[0020] The method of the present invention adopts solvent to disperse and deposit lithium ion battery positive electrode material. In the actual production process, lithium battery manufacturers adopt self-rotating and revolving stirrers for dispersion, while the present invention adopts ultrasonic dispersion or mechanical stirring dispersion in the laboratory to simulate the process of nanoparticle agglomeration when battery slurry is dispersed, and then the specific particle size is detected after large particles are enriched by deposition. The method and process sample preparation method are simple, the detection equipment is popular, and the operability is strong. The required material is far less than the traditional sieve screening method, and the particle size distribution of agglomerated large particles in the slurry can be accurately detected. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] The present invention will be further described below in conjunction with the accompanying drawings.
[0022] Figure 1 is an electron microscope image of Example 1 of the present invention;
[0023] Figure 2 is an electron microscope image of Example 2 of the present invention;
[0024] Figure 3 is an electron microscope image of Example 3 of the present invention;
[0025] Figure 4 It is the electron microscope image of comparative example 1 of the present invention;
[0026] Figure 5 It is the electron microscope picture of comparative example 2 of the present invention. DETAILED DESCRIPTION
[0027] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0028] Example 1
[0029] S1. Deposition: 50 g of lithium iron phosphate positive electrode powder was added to 50 mL of N-methylpyrrolidone in a 100 mL beaker, and a cantilever stirrer was used to stir and disperse the mixture for 30 min. The mechanical stirring speed was 1000 rpm. After the mixture was allowed to stand for 2 min, the upper solid-liquid mixture was poured out to obtain a deposited powder.
[0030] S2. Repeated dispersion and deposition: Repeatedly disperse and deposit the deposited powder 3 times, adding 30 mL of N-methylpyrrolidone solvent to the deposited powder each time, and disperse it with a cantilever stirrer for 10 minutes, with a mechanical stirring speed of 1000 rpm, and let it stand for 2 minutes to obtain a deposited powder, and finally obtain the sample to be tested.
[0031] S3. Laser particle size analyzer detection: The sample to be tested obtained in S2 is dispersed in N-methylpyrrolidone and added into a laser particle size analyzer to test the particle size distribution.
[0032] S4. Scanning electron microscope detection: The sample to be tested obtained in S2 is filtered and dried, and adhered to the sample stage of the scanning electron microscope with a conductive tape. The particle size of large particles is observed under the scanning electron microscope.
[0033] Table 1 is the data obtained by the laser particle size analyzer in Example 1, and the electron microscope image of the powder material of batch S-3 is shown in Figure 1 .
[0034]
[0035] Example 1 is the test result after repeated deposition 3 times using NMP solvent. The results show that D99>10μm, and large agglomerated particles larger than 10μm can be clearly seen in the electron microscope image, proving that large particle agglomeration exists during the stirring process, and the particle size range can be confirmed, which can better detect the agglomerated large particles of the positive electrode material.
[0036] Example 2
[0037] S1. Deposition: Take 25 g of lithium iron phosphate positive electrode powder and add 80 mL of ultrapure water to a 100 mL beaker. Use a cantilever stirrer to stir and disperse for 30 minutes to obtain a mixture. The mechanical stirring speed is 1000 rpm. After the mixture is allowed to stand for 3 minutes, pour out the upper solid-liquid mixture to obtain a deposited powder.
[0038] S2. Repeated dispersion and deposition: Repeatedly disperse and deposit the deposited powder 3 times, adding 30 mL of ultrapure water to the deposited powder each time, and disperse it with a cantilever stirrer for 10 minutes, with a mechanical stirring speed of 1000 rpm, and let it stand for 3 minutes to obtain a deposited powder, and finally obtain the sample to be tested.
[0039] S3. Laser particle size analyzer detection: Disperse the sample to be tested in ultrapure water and add it to the laser particle size analyzer to test the particle size distribution.
[0040] S4. Scanning electron microscope detection: Filter and dry the sample to be tested, adhere it to the scanning electron microscope sample stage with conductive tape, and observe the particle size of large particles under the scanning electron microscope.
[0041] Table 2 is the data obtained by the laser particle size analyzer in Example 2, and the electron microscope image of the powder material of batch Y-1 is shown in Figure 2 .
[0042]
[0043] In Example 2, ultrapure water is used as a solvent for mechanical stirring, dispersion and deposition. According to the particle size distribution and electron microscope results, large agglomerated particles can be effectively obtained, and the enrichment of agglomerated particles can be achieved. The enrichment effect is similar to that of Example 1.
[0044] Example 3
[0045] S1. Deposition: Take 20 g of lithium iron phosphate positive electrode powder and add 40 mL of anhydrous ethanol to a 100 mL beaker. Use ultrasonic dispersion for 30 minutes to obtain a mixture. The ultrasonic frequency is 53 KHz. After the mixture is allowed to stand for 3 minutes, pour out the upper solid-liquid mixture to obtain a deposited powder.
[0046] S2. Repeated dispersion and deposition: Repeatedly disperse and deposit the deposited powder 3 times, adding 20 mL of anhydrous ethanol to the deposited powder each time, and disperse it by ultrasound for 10 minutes at an ultrasonic frequency of 53 KHz, and let it stand for 3 minutes to obtain a deposited powder, and finally obtain the sample to be tested.
[0047] S3. Laser particle size analyzer detection: Disperse the sample to be tested in anhydrous ethanol and add it to the laser particle size analyzer to test the particle size distribution.
[0048] S4. Scanning electron microscope detection: Filter and dry the sample to be tested, adhere it to the scanning electron microscope sample stage with conductive tape, and observe the particle size of large particles under the scanning electron microscope.
[0049] Table 3 is the data obtained by the laser particle size analyzer in Example 3, and the electron microscope image of the powder material of batch S-6 is shown in Figure 3 .
[0050]
[0051] In Example 3, anhydrous ethanol is used as the solvent for ultrasonic dispersion deposition. According to the particle size distribution and electron microscope results, large agglomerated particles can be effectively obtained, and the enrichment of agglomerated particles can be achieved.
[0052] Example 4-Example 8
[0053] Different from Example 3, the number of repeated depositions using the same batch of lithium iron phosphate positive electrode powder was adjusted to 1, 2, 3, 4 and 5 times, and the other steps were the same as Example 3. Table 4 shows the data obtained by the laser particle size analyzer of Examples 4 to 8.
[0054]
[0055] It can be seen from the results of different deposition times in Examples 4 to 8 that when the number of dispersed depositions is too few, it is impossible to simulate the actual stirring environment to obtain large agglomerated particles. When the number of dispersed depositions is too many, the sample amount gradually decreases, making it difficult to meet the detection requirements of the laser particle size analyzer and unable to detect.
[0056] Example 9-Example 12
[0057] Different from Example 3, the single standing time in the repeated deposition process of the same batch of lithium iron phosphate positive electrode powder was adjusted to 1 min, 2 min, 3 min and 4 min, and the other steps were the same as Example 3. Table 5 shows the data obtained by the laser particle size analyzer of Examples 9 to 12.
[0058]
[0059] The results of Example 9-Example 12 show that if the single standing time is too short, the agglomerated large particles cannot be completely deposited, and the obtained test samples are small, which does not meet the detection requirements. If the standing time is too long, a large number of small particles will be deposited in the test samples, reducing the proportion of large particles, and D99 will be around 10μm, and large particles cannot be detected.
[0060] Comparative Example 1
[0061] The difference from Example 1 is that the lithium iron phosphate positive electrode powder is not subjected to deposition treatment.
[0062] S1. Dispersion: Take 50 g of lithium iron phosphate positive electrode powder and add 50 mL of N-methylpyrrolidone to a 100 mL beaker, and use a cantilever stirrer to stir and disperse for 30 minutes to obtain a mixture. The mechanical stirring speed is 1000 rpm.
[0063] S2. Laser particle size analyzer detection: Add the mixture into the laser particle size analyzer to test the particle size distribution.
[0064] S3. Scanning electron microscope detection: Filter and dry the sample to be tested, adhere it to the scanning electron microscope sample stage with conductive tape, and observe the particle size of large particles under the scanning electron microscope.
[0065] Table 6 is the data obtained by the laser particle size analyzer of Comparative Example 1, and the electron microscope image of the powder material of batch S-1 is shown in Figure 4 .
[0066]
[0067] Comparative Example 1 is to directly take powder for dispersion and then test. Compared with Example 1, the results show that no agglomerated particles larger than 10 μm can be detected. Direct dispersion detection cannot simulate the effect of forming large particles in actual production, and cannot accurately detect agglomerated large particles.
[0068] Comparative Example 2
[0069] The difference from Example 1 is that the lithium iron phosphate positive electrode powder is processed by ultrasonic screening.
[0070] S1. Screening: Take 1 kg of S-1 batch of lithium iron phosphate positive electrode powder after stirring the actual production slurry, and screen it through a 1600-mesh sieve to obtain large-particle powder.
[0071] S2. Scanning electron microscope detection: Filter and dry the large particle powder, adhere it to the scanning electron microscope sample stage with conductive tape, and observe the particle size of the large particle material under the scanning electron microscope.
[0072] Since the sample was screened through a sieve, laser particle size detection could not be performed due to the small amount of sample.
[0073] Table 7 shows the sample size of large-particle powder obtained after screening in Comparative Example 2. Figure 5 .
[0074]
[0075] The comparative example adopts the traditional screening and then detection method. Since there are few large agglomerated particles in a small amount of material, direct sampling and detection are impossible. Although the screening method can concentrate the large agglomerated particles, the sample amount is large and the reagent detection operation is complicated. Even if 1kg of lithium iron phosphate positive electrode powder after stirring of the actual production slurry is used, the sample amount obtained after screening still does not meet the laser particle size detection requirements.
[0076] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.
[0077] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for testing the particle size distribution of a lithium-ion battery positive electrode material, characterized in that: The following steps are involved: S1. Deposition: Take lithium iron phosphate positive electrode powder material, disperse it in a solvent to obtain a mixture, let the mixture stand for 2-3 minutes, pour out the upper solid-liquid mixture, and obtain a deposited powder; S2, repeated dispersion and deposition: repeat the dispersion and deposition operation steps of S1 for the deposited powder, repeat the dispersion and deposition 2-4 times to prepare the sample to be tested; S3, laser particle size analyzer detection: the sample to be tested obtained in S2 is dispersed in a solvent and added to a laser particle size analyzer to test the particle size distribution; S4, scanning electron microscope detection: filter and dry the sample obtained in S2, adhere it to the scanning electron microscope sample stage with conductive tape, and observe the particle size of large particles under the scanning electron microscope; The dispersion method in S1 is one of ultrasonic dispersion and mechanical stirring dispersion, and ultrasonic dispersion or mechanical stirring dispersion is used to simulate the process of nanoparticle agglomeration when the battery slurry is dispersed.
2. The method for testing the particle size distribution of a lithium-ion battery positive electrode material according to claim 1, characterized in that: The sampling amount of the lithium iron phosphate positive electrode powder material is 20-50g.
3. The method for testing the particle size distribution of a lithium ion battery positive electrode material according to claim 1, characterized in that: The solvent is one of ultrapure water, anhydrous ethanol and N-methylpyrrolidone.
4. The method for testing the particle size distribution of a lithium-ion battery positive electrode material according to claim 1, characterized in that: The mass ratio of the lithium iron phosphate positive electrode powder material to the solvent in the mixture is 1:1-4.
5. The method for testing the particle size distribution of a lithium-ion battery positive electrode material according to claim 1, characterized in that: The ultrasonic frequency is 53 KHz, or the rotation speed of the mechanical stirring is 1000 rpm.
6. The method for testing the particle size distribution of a lithium ion battery positive electrode material according to claim 1, characterized in that: The dispersion time in S1 is 30 min.
7. The method for testing the particle size distribution of a lithium-ion battery positive electrode material according to claim 1, characterized in that: The single solvent dosage in the repeated dispersion deposition is 20-30 mL.
8. The method for testing the particle size distribution of a lithium-ion battery positive electrode material according to claim 1, characterized in that: The single dispersion time in the repeated dispersion deposition is 10 minutes, and the single standing time is 2-3 minutes.
9. The method for testing the particle size distribution of a lithium-ion battery positive electrode material according to claim 1, characterized in that: The particle size of the sample to be tested is 0.1-55 μm.
Citation Information
Patent Citations
Method for detecting oversize particles in diamond micro-powder
CN117848929A
Positive active material, positive pole piece, battery and electric device
CN118693274A
Cited By
Method for measuring particle size of slurry by laser diffraction method
CN121141453A